Comparison of Outcomes After Primary Laparoscopic Versus Open Approach for T1b/T2 Gallbladder Cancer - Cao, Jiasheng; Wang, Yong; Zhang, Bin; Hu, Jiahao; Topatana, Win; Li, Shijie; Juengpanich, Sarun; Lu, Ziyi; Cai, Xiujun; Chen, Mingyu (Frontiers in Oncology, 2021)
Objectives: Primary laparoscopic approach (PLA) for T1b/T2 gallbladder cancer (GBC) remains contradicted. We aimed to compare the perioperative and long-term outcomes after PLA versus open approach (OA) for T1b/T2 GBC. Methods: Patients with resected T1b/T2 GBC were selected from our hospital between January 2011 and August 2018. Overall survival (OS), disease-free survival (DFS), and several secondary outcomes were used to evaluate safety and effectiveness. Subgroup analyses were performed to identify significant risk factors for OS/DFS in GBC patients undergoing PLA/OA. Results: A total of 114 patients who underwent OA (n = 61) or PLA (n = 53) were included in the study. The percent of PLA cases was increased over time from 40.0% in 2011 to 70.0% in 2018 (P < 0.05). There was no significant difference in OS [hazard ratio (HR), 1.572; 95% confidence interval (CI), 0.866-2.855; P = 0.13] and DFS (HR, 1.225; 95% CI, 0.677-2.218; P = 0.49). No significance was found for intraoperative drainage placement (P = 0.253), intraoperative blood loss (P = 0.497), operation time (P = 0.105), postoperative hospitalization (P = 0.797), positive LNs (P = 0.494), total harvested LNs (P = 0.067), and recurrence rates (P = 0.334). Subgroup analyses demonstrated no significance of conversion rates after PLA (all P > 0.05). Patients undergoing PLA with good/poor OS would have similar recurrence rates (P = 0.402). Positive LNs (P = 0.032) and tumor differentiation (P = 0.048) were identified as risk factors for OS after PLA, while positive LNs (P = 0.005) was identified for OS after OA. Moreover, age (P = 0.013), gallbladder stone (P = 0.008), tumor size (P = 0.028), and positive LNs (P = 0.044) were potential risk factors for DFS after OA. Conclusions: PLA for T1b/T2 GBC was comparable to OA in terms of perioperative and long-term outcomes. Less positive LNs and well differentiated tumors were independent predictors for better OS after PLA, and less positive LNs was also identified for better OS after OA. Additionally, younger age, without gallbladder stone, smaller tumor size, and less positive LNs were potential risk factors for better DFS after OA.